Healthy Aging in Place: Supporting Rural Seniors' Health Needs - Juanita R. Bacsu; Bonnie Jeffery; Shanthi Johnson; Diane Martz; Nuelle Novik; Sylvia Abonyi (Rural Nurse Organization; Binghamton University, 2012)
Purpose To examine the key determinants that support healthy aging in rural communities. Sample Forty- two participants aged 65 and older were recruited from two rural communities in Saskatchewan, Canada. Methods Using an ethnographic methodological approach, data was collected through semi-structured interviews, field notes and participant observation notes. Cantor's (1989) Social Care Model was used as the theoretical framework for exploring the supports that facilitate rural healthy aging. Findings Healthy aging among rural seniors extends significantly beyond access to physicians and formal health care. Eight key themes related to healthy aging were identified: housing; transportation; healthcare; finances; care giving; falls; rural communities; and support systems. Conclusions While there is evidence of poor health among rural seniors, little research has examined healthy aging or the determinants that facilitate healthy aging in rural communities. In addressing rural seniors' health needs, this study provides a fundamental basis for developing effective interventions and innovative public policy options to support rural healthy aging. Keywords: Rural Health, Social Support, Rural Aging, Public Policy, Disparities